Development of low-calcium fly ash-based geopolymer mortar using nanosilica and hybrid fibers. Issue 15 (1st August 2021) - Chen, Keyu; Wu, Dazhi; Chen, HaiXiang; Zhang, Guoqing; Yao, Ruolan; Pan, Chonggen; Zhang, Zhenying
Abstract: Fly ash has been widely explored in alkali-activated concrete technology as a precursor; however, it suffers sudden brittle failure and requires heat activation for early-strength development. Previous studies have demonstrated that these shortcomings can be overcome by adding nanosilica and various types of fibers. However, they were mainly focused on improving the mechanical properties, but there is no clear understanding of the durability and microstructural changes. Therefore, this study systematically addresses the effects of nanosilica sol and hybrid fibers (steel and polypropylene fibers) on the workability, porosity, flexural/compressive strength development, flexural toughness, crack resistance, and durability (subjected to sulfuric acid of pH = 1, 5% sodium sulfate, and 3.5% seawater attacks) of fly ash-based mortars cured at ambient environments. The results demonstrate that nanosilica and hybrid fibers have acceptable simultaneous effects on the properties of mortar. Although they both reduce fluidity, nanosilica improves the pore enlargement caused by fiber materials; thus, it greatly improves the mechanical properties of mortar. The flexural toughness of the mortar with nanosilica and hybrid fibers was approximately 200% higher than that of the pure-fly ash. Only approximately 58.25 mm 2 microcracks were observed during the early crack detection, and the residual strength also improved under chemical solution attack. The microstructures were studied by field-emission scanning electron microscopy with energy-dispersive X-ray spectroscopy, X-ray diffraction/Rietveld method, and nanoscale 3D X-ray microscopy. The nanosilica enhanced the reactivity of the precursors and refined the pore structure of the mortar due to the changes in the crystalline and amorphous phases, and the hybrid fibers produced composites with good internal characteristics and strong fiber/matrix interfacial bonding.